Exploring the impact of a story-based teacher training programme on language and early literacy in 4- and 5-year-olds: A description of the isiXhosa children in the study sample. Wordworks: Cape Town. - Cain, Kate; O'Carroll, Shelley; Oakhill, Jane; Klop, Daleen; Smith, Annelien (Wordworks, 2023)
This is the fourth in a series of five research briefs that explore the impact of Little Stars, a story-based teacher training programme on language and early literacy in 4- and 5-year-olds. This brief describes the isiXhosa children in the study, their home learning environment and their early development across different developmental domains.
More information about the Little Stars training programme and materials can be found at: www.wordworks.org.za
Keywords: Early language; Early literacy; South Africa; isiXhosa; Narrative; Vocabulary; ELOM